ANALISIS EVALUATIF PELAKSANAAN SUSCATIN BERBASIS MODEL CIPP DI KUA KECAMATAN TIDORE KEPULAUAN - Abubakar, Fatum; Rahman, Nur Azizah; Ubaedillah; Ali, Mirnawati; Barora, Siti (Program Studi Hukum Keluarga Fakultas Syariah UIN Datokarama Palu, 2025)
This study analyzes the practice of SUSCATIN at KUA in East Tidore, South Tidore, and Tidore Regency. The analysis uses Bimas Decree No. DJ.II/491 of 2009 which has been in effect for a long time. This study is a field study using the CIPP Evaluation Model (Context, Input, Process, and Product) by Daniel Stufflebeam. Data collection was conducted through in-depth interviews with related parties: Head of KUA, Religious Counselors, and SUSCATIN participants. Documentation was obtained from the SUSCATIN activity archives and KUA Internal reports. The results of this study indicate that in terms of contextual evaluation, the SUSCATIN program has not fully met the needs of prospective brides and grooms because it is carried out incidentally, so it does not address the problems of couples who are going to get married. While the input evaluation is expected to provide support for the SUSCATIN system as a strategy, curriculum identification and SUSCATIN instructor education qualifications, but it is unable to accommodate the needs of the participants. In the evaluation process is still conventional, time constraints and monotonous teaching methods and participant participation has not been achieved optimally so that obstacles are not resolved properly. Thus, the evaluation of the SUSCATIN product is expected to increase the knowledge and skills of participants, but this program has not been running optimally and is still limited, which makes it impossible to create a harmonious and happy family.